Opportunities and Challenges of the Human Microbiome in Ovarian Cancer - Cheng, Huiyan; Wang, Zhichao; Cui, Lifeng; Wen, Yan; Chen, Xiuhua; Gong, Fengyan; Yi, Huanfa (Frontiers in Oncology, 2020)
Ovarian cancer is the most lethal malignancy among gynecological cancers worldwide. Most ovarian cancer patients are diagnosed at an advanced stage because of non-specific clinical symptoms. The human microbiome plays a crucial role in maintaining the normal physiological and pathological state of the body. With the development of technologies such as DNA and 16S rRNA sequencing, an increasing number of findings on the role of microbiome in cancers are being reported. Microbiome abnormalities are increasingly associated with diseases, including cancer development, and response to therapies. Some studies have shown the relationship between microbiome changes and ovarian cancer. However, the mechanisms underlying this relationship are not yet fully understood. Here, we summarize the key findings in this regard by focusing on estrogen metabolism and host recognition receptors in microorganisms and changes in the gut or pelvic microbiome in patients with ovarian cancer. We further discuss the potential of using the microbiome as a novel biomarker for cancers. We also highlight the possibility to use microorganisms as a treatment modality to enhance the immune system, activate anti-tumor response, mediate chemotherapy resistance, and ameliorate the adverse effects of the treatment.